Liver abscess as a complication of Gastric Roux Y Bypass: Case report (Research, Society and Development, 2023)
Obesity has been presented as a disease associated with high morbidity, due to the involvement of obesity per se, and the worsening of other associated morbidities such as type 2 Diabetes Mellitus, systemic arterial hypertension, dyslipidemia, coronary heart disease, obstructive sleep apnea, psychiatric disorders within others. Obesity treatment begins with lifestyle changes, physical activity, nutritional support; and can extend to support with a team of medical specialties, such as endocrinology. Despite the multidisciplinary nature of the initial treatment, the number of patients who are unsuccessful in losing weight and consequently improving their morbidity and quality of life is significant. As an additional therapy in these cases, bariatric surgery has emerged as a procedure that is gaining ground. The proposed surgeries present different mechanisms to obtain the final result, including malabsorptive, restrictive and mixed. Regardless of the surgical procedure proposed, there is always the possibility of intra-operative or post-operative complications; These include liver abscesses, surgical wound infections, hemorrhages and fistulas in the digestive system. This case report purpose is to report a rare case of liver abscess after a laparoscopic bariatric surgery.